PENGARUH PEMBERIAN REBUSAN AIR DAUN SIRIH DAN AGAR– AGAR LIDAH BUAYA TERHADAP KEJADIAN KEPUTIHAN PADA REMAJA PUTRI DI UPT PUSKESKAS TIRTAYASA TAHUN 2025 - Fitriyawati, Fitriyawati; Magdalena Tri Putri; Putri Agus Febriyani (Journal of Innovation Research and Knowledge, 2025)
This research discusses the Economic Potential of Marine Resources. This research uses descriptive qualitative research. This research was conducted in Southwest Mauku Regency, Liran Island in May-June 2024. This research uses coastal communities on Liran Island as research subjects. Research subjects were selected by collecting data. Data was obtained through interviews, observation and documentation. Furthermore, the data from the results of this research were then analyzed by data reduction, data presentation, then drawing conclusions. The results of this research indicate that marine resources that have great potential to be developed in Southwest Maluku Regency, Liran Island, are fisheries and marine resources (seaweed). However, its management has not been carried out optimally, because there are several inhibiting factors in its management, namely: lack of government contribution, low level of community understanding, and the character of the community so that it has not been able to support the implementation of Marine Resources.